Sistem Informasi Sidang Seminar Proposal dan Skripsi Berbasis Web dengan Pendekatan Metode Waterfall - Muhammad Farid Arshal Afandi; Ahmad Jazuli; Esti Wijayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The scheduling of proposal seminars and thesis defenses is a crucial process completely of student studies in the informatics engineering study program. However, this process often faces several challenges, such as delayed information, manual data accumulation, and a lack of transparency in schedule and examiner selection. To address these issues, the Laravel framework was chosen for the design of this web-based system, aiming to simplify the administration and scheduling processes for proposal seminars and thesis defenses. Laravel was selected due to its support for structured, secure, and efficient system development. This web-based system utilizes PHP and SQL for database management. The development methodology used is Waterfall, which adopts a sequential and systematic approach, starting from the requirement, design, implementation, verification, and maintenance stages. Each stage is done in a structured manner to ensure that all needs have been met before moving on to the next stage. System implementation using the Laravel framework as the backend foundation with responsive interface design. The case study was conducted at the Informatics Engineering Study Program of Universitas Muria Kudus. The results of testing indicate that the system improves data processing efficiency, accelerates information delivery, and minimizes errors in the registration and scheduling processes. With implementation of this system, academic procedures are expected to become more orderly, transparent, and well-structured. The test results show that the system is able to improve efficiency, as well as reduce administrative errors in the registration and scheduling process. All users are already interrelated in this registration process, starting from students, lecturers, coordinators, operators.